Family Thrombidae Sollas, 1888. Pp. 163-164 - Uriz, M.J. (In: Hooper, J.N.A., van Soest, R.W.M. (eds) Systema Porifera. A Guide to the Classification of Sponges (2 volumes). Kluwer Academic/Plenum Publ., New York, 2002)
Thrombidae Sollas (Demospongiae, Astrophorida) contains only a single genus and five species to date, characterized by peculiar spiny triaenes (acanthotriaenes) of a size intermediate between that of megascleres and microscleres, often with clads divided dichotomously or trichotomously. Microscleres, when present, are streptasters (amphiasters). No clear relationships of this family with any other sponge group have been established.
The PDF supplied here is a proof - NOT the definitive printed text - of a chapter of the Systema Porifera